Effects of Sulfated Modification on the Structural Characterization and Antioxidant Activities of Coconut (Cocos nucifera L.)Haustorium Polysaccharide - Jintao KAN; Zhenglin PI; Kaili YANG; Jinhao ZHAO; Xiaoyan LIU; Yufeng ZHANG (Shipin gongye ke-ji, 2024)
To investigate the effect of sulfated modification on the structure and function of coconut haustorium polysaccharide (CHP), three kinds of sulfated coconut haustorium polysaccharides (SCHP-2, SCHP-3, and SCHP-4) were prepared using sulfation reagents containing different ratios of chlorosulfonic acid and pyridine (v/v, mL/mL: 1/2, 1/3, and 1/4) after extracting CHP from the raw materials of coconut haustorium, and their basic chemical compositions, structural characteristics and antioxidant activity in vitro were compared and analyzed. Results showed that all three sulfation reagents were able to modify CHP (characteristic peaks of S=O and C-O-S were observed near 1100~1250 cm−1 and 820 cm−1 in infrared spectra, respectively), and the degree of substitution (DS) was the highest (0.75) at the ratio of chlorosulfonic acid and pyridine for 1/2. The total sugar, uronic acid content, and molecular weight of the three SCHP decreased, and the molar content of monosaccharides also changed when comparing with that of CHP. The thermal stability had slightly weakened as well (the degradation temperature of polysaccharides decreased from 211.17 ℃ and 282.01 ℃ of CHP to 194.86~207.70 ℃ and 233.35~262.46 ℃ of SCHP, respectively). The results of antioxidant experiments in vitro showed that the scavenging activity of SCHP on DPPH and hydroxyl radicals was lower than that of CHP, and the larger the DS was, the more obvious the decrease in activity was. In terms of the ABTS+ radicals scavenging ability and ferrous ions chelating activity, increasing DS could enhance the activity of SCHP. At 8 mg/mL, the ABTS+ radicals scavenging rate (54.82%) and ferrous ions chelating rate (15.59%) of SCHP-2 were significantly (P<0.05) higher than CHP (33.67% and 8.86%). These results would provide the support for the modification and functional application of coconut haustorium polysaccharides.